Monitoring analysis of two pavement sections of highway BR-448/RS included in the Asphalt Thematic Network Project - Kern, Camila; Bock, André Luiz; Núñez, Washington Peres; Ceratti, Jorge Augusto Pereira (Transportes, 2020)
Highways are the mode of transport used for the transportation of the majority of loads and passengers in Brazil; however, the lack of conservation of pavements has caused several economical losses to the country. Only through suitable pavement management the rehabilitation measures taken might ensure a satisfactory level of service. The present research aimed at evaluating the performance of two pavement sections of the federal highway BR-448/RS, in southern Brazil. For three years, the evolution of the pavement structural capacity and functional condition were followed in order to propose performance trends. Deflections, permanent deformations, and surface defects surveys scarcely varied and were quite low due to the thick asphalt layers used (19 cm). On the other hand, segregation of the asphalt mixture was observed when the final layer was laid. That segregation affected pavement texture, reduced tire-road friction, and caused the formation of surface water films; thus, reducing the road safety. In general, the proposed trend lines predicted quite accurately the pavement performance throughout the period evaluated and will be used in the MeDiNa software database for the creation of a new Brazilian pavement design method.